(untitled) (Bulletin KNOB, 2004)
Amersfoort is a town with roots in the Middle Ages. In the late nineteenth and late twentieth century the town was connected to the national railway network and the European motorway network respectively. In 1982 it became a town designated for expansion. The number of inhabitants had to be doubled to 120,000. For the municipal authorities this was an immense task. Additional problems were the historical town centre within a stone’s throw from the area covered by the plan, and opposite the railway an area with run-down (chemical) industry and considerable soil pollution. The municipal authorities proceeded with energy and made a structural plan to anticipate any speculation. Besides, a public-private organisation was set up, in which all the relevant parties were represented. In 1989 the ’Centraal Stadsgebied Amersfoort’ development plan (for the city centre area of Amersfoort) was drawn up. This plan met with strong opposition from the population, politics and some physical planners. The national authorities appreciated the broad approach of the total plan and gave financial support. It also became an example for similar plans in the country. During the long duration of the plan substantial changes had to be carried out. This was partly due to the dimensional objections from among the population (’Manhattan on the Eem’), but also to the changing economic conditions and the fluctuations in the real-estate market. Notably the high-rise buildings and the large-scale projects were levelled down or shelved. The subproject ’Eem quarter’ (dealt with in detail in this article) was not executed at all and is still under development now in a fundamentally changed form.